Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006439.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Chromoscopy versus conventional endoscopy for the detection of polyps in the colon and rectum

Abstract: There appears to be strong evidence that chromoscopy enhances the detection of neoplasia in the colon and rectum. Patients with neoplastic polyps, particularly those with multiple polyps, are at increased risk of developing colorectal cancer. Such lesions, which presumably would be missed with conventional colonoscopy, could contribute to the interval cancer numbers on any surveillance programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 31 publications
0
32
0
4
Order By: Relevance
“…Our findings are fully consistent with those of Le Rhun et al (25), who found that although a high-definition colonoscopy with chromoscopy (indigo) increased the detection of flat adenomas compared to a standard definition colonoscopy, the overall ADR was not significantly improved in a population at increased risk for colonic neoplasia. In contrast, a Cochrane database systematic review reports that chromoscopy with indigo carmine is likely to yield significantly more patients with at least one neoplastic lesion (OR 1.67 [CI 1.29-2.15]) and significantly more patients with three or more neoplastic lesions (OR 2.5 [CI 1.5-4.4]) (26). However, it is important to quote that, currently, digital chromoendoscopy (such as i-SCAN, NBI and FICE) has not shown in any metaanalysis to be superior to SRWL for detection of adenomas, so both techniques (digital chromoendoscopy vs. dye chromoendoscopy) could have different detection yield.…”
Section: Discussionmentioning
confidence: 93%
“…Our findings are fully consistent with those of Le Rhun et al (25), who found that although a high-definition colonoscopy with chromoscopy (indigo) increased the detection of flat adenomas compared to a standard definition colonoscopy, the overall ADR was not significantly improved in a population at increased risk for colonic neoplasia. In contrast, a Cochrane database systematic review reports that chromoscopy with indigo carmine is likely to yield significantly more patients with at least one neoplastic lesion (OR 1.67 [CI 1.29-2.15]) and significantly more patients with three or more neoplastic lesions (OR 2.5 [CI 1.5-4.4]) (26). However, it is important to quote that, currently, digital chromoendoscopy (such as i-SCAN, NBI and FICE) has not shown in any metaanalysis to be superior to SRWL for detection of adenomas, so both techniques (digital chromoendoscopy vs. dye chromoendoscopy) could have different detection yield.…”
Section: Discussionmentioning
confidence: 93%
“…Эта рекомендация обосновывается дополнительными финансовыми затратами, связанными с красителями, удалением образований, гистопатологическим исследовани-ем дополнительных не неопластических пораже-ний, увеличением общего времени вмешательства и с отсутствием доказательств, подтверждающих увеличение выявления неоплазий с высокой сте-пенью дисплазии. Однако, по данным Кокрей-новского обзора [10], проанализировавшего пять рандомизированных клинических исследований (РКИ), оценившего роль прицельной хромоско-пии в выявлении колоректальных поражений при отсутствии полипоза и колита, было показано, что выполнение тотальной хромоскопии значительно увеличило число пациентов с, как минимум, од-ним выявленным полипом (соотношение шансов По данным японского эндоскопического фо-рума, прошедшего в 2014 г. в Отару (Хоккайдо), хромоскопия позволяет обеспечить большее об-наружение небольших полипов, плоских пораже-ний, аденом и количество пациентов, имеющих по крайней мере одну аденому, при этом в осно-вном в правой половине ТК [25]. По данным по-следнего Кокрейновского обзора [11], существу-ют убедительные доказательства того, что хромос-копия улучшает обнаружение неоплазии в толстом кишечнике.…”
Section: оригінальні дослідженняunclassified
“…Studies have demonstrated that the eff ectiveness of colonoscopy is strongly associated with the endoscopist ' s adenoma detection rate ( 23 ). Adenoma detection can be improved through training ( 24 ) or use of adjunctive imaging techniques, such as chromoendoscopy ( 25 ). Unfortunately, while easy to implement, optical or electronic chromoendoscopy has not demonstrated a clear benefi t over high-defi nition white light endoscopy for detection of neoplasia ( 26 ).…”
Section: Conflict Of Interestmentioning
confidence: 99%